2021
DOI: 10.3389/fcell.2021.673395
|View full text |Cite
|
Sign up to set email alerts
|

“Janus-Faced” α-Synuclein: Role in Parkinson’s Disease

Abstract: Parkinson’s disease (PD) is a pathological condition characterized by the aggregation and the resultant presence of intraneuronal inclusions termed Lewy bodies (LBs) and Lewy neurites which are mainly composed of fibrillar α-synuclein (α-syn) protein. Pathogenic aggregation of α-syn is identified as the major cause of LBs deposition. Several mutations in α-syn showing varied aggregation kinetics in comparison to the wild type (WT) α-syn are reported in PD (A30P, E46K, H 50Q, G51D, A53E, and A53T). Also, the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 446 publications
(535 reference statements)
1
5
0
Order By: Relevance
“…The NAC domain is believed to be responsible for α-syn aggregation, leading to the formation of β-sheet-rich amyloid fibrils. 4…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The NAC domain is believed to be responsible for α-syn aggregation, leading to the formation of β-sheet-rich amyloid fibrils. 4…”
Section: Introductionmentioning
confidence: 99%
“…It results in the loss of dopaminergic neurons in the substantia nigra pars compacta. 4,5 Besides PD, there is a group of disorders characterized by the accumulation of inclusions enriched in a-syn called synucleinopathies, including Lewy body dementia (LBD), multiple system atrophy (MSA), and pure autonomic failure (PAF). 6 Due to the central role of a-syn in the pathology of PD and other forms of synucleinopathies, the lack of an early and definitive antemortem diagnosis for synucleinopathies, and effective treatment, numerous studies have been focused on targeting a-syn for diagnosis and therapeutics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main function of α-synuclein may be to regulate the activity of synaptic vesicles, the release of neurotransmitters, and the recycling of synaptic vesicles. In addition, studies have shown that α-synuclein is involved in neuronal Golgi and vesicle transport, membrane structure regulation, lipid metabolism, mitochondrial fusion, DNA repair, and cognitive functions [4]. The structure of α-synuclein is unstable, and the αhelix conformer is easily replaced by a β-sheet.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple mutations present in family members with PD are known, including autosomal dominant ( SNCA , LRRK2 , VPS35 ) and recessive ( PARK2 , PINK1 , DJ-1 ) forms [ 25 ], although many additional risky loci have been identified [ 26 , 27 ]. The overexpression (duplication or triplication) or mutation of the SNCA gene is known to be a cause of familial PD [ 25 , 28 , 29 ]. Most SNCA point mutations are associated with the early onset of disease.…”
Section: Introduction To Pd Pathogenesismentioning
confidence: 99%